Facilitating family needs and support at the end of life in hospital: A descriptive study. (March 2022) - Bloomer, Melissa J; Poon, Peter; Runacres, Fiona; Hutchinson, Alison M
Background: Caring for family members of dying patients is a vital component of end-of-life care, yet family members' needs at the end of life may be unmet. Aim: To explore hospital clinician assessment and facilitation of family needs and practices to support families at the end of life. Design: Descriptive study utilising a retrospective medical record audit. Setting and Sample: Undertaken in a large public hospital, the sample included 200 deceased patients from four specialities; general medicine ( n = 50), intensive care ( n = 50), inpatient palliative care ( n = 50) and aged rehabilitation ( n = 50). Data were analysed according to age; under 65-years and 65-years or over. Results: Deceased patients' mean age was 75-years, 60% were Christian and Next-of-Kin were documented in 96% of cases. 79% spoke English, yet interpreters were used in only 6% of cases. Formal family meetings were held in 64% of cases. An assessment of family needs was undertaken in 52% of cases, and more likely for those under 65-years ( p = 0.027). Cultural/religious practices were supported/facilitated in only 6% of all cases. Specialist palliative care involvement was more likely for those aged 65-years or over ( p = 0.040) and social work involvement more likely for those under 65-years ( p = 0.002). Pastoral care and bereavement support was low across the whole sample. Conclusions: Prioritising family needs should be core to end-of-life care. Anticipation of death should trigger routine referral to support personnel/services to ensure practice is guided by family needs. More research is needed to evaluate how family needs assessment can inform end-of-life care, supported by policy.